Assessing the perceptions of a biostatistics and epidemiology module: Views of Year 2 medical students from a Malaysian university. A cross-sectional survey - Daher, Aqil M.; Amin, Farzana (BMC, 2010)
Background In the era of evidence based medicine, biostatistics and epidemiology are considered as the main elements aiding the health professional to design a research study, understand the literature, and make decisions about patient care. The aim of the study is to explore students' perception about this subject because it plays an important role in determining educational outcome. Methods Data were collected from a self-administered questionnaire distributed among 164 Year 2 medical students. The 5-point Likert scale anchored by Strongly disagree = 1 and Strongly agree = 5 included 36 questions in four domains designed to assess the perception of a biostatistics and epidemiology module amongst students. Results 138 students with ages ranging from 20 to 24 years (Mean = 20.7; SD = 0.62) returned their responses to the questionnaire. This was a response rate of 84.14%. Of the 138 students, 80.7% realized the relevance of the subject to real health issues at the end of the module, while 89.8% believed the module focused on interpretation more than calculation. More than three quarters (78.1%) agreed that lack of practicing exercises was the cause for declining interest in the subject, while only 26.1% believed that lectures were not interesting. Another three quarters (75.4%) believed that there were too many lectures for one day of teaching activities, while 84.6% recommended practical sessions for designing research and data collection. Conclusions This study found that students perceived the relevance of biostatistics and epidemiology to real health issues. The major cause of poor interest in the subject was attributed to the short duration of the course, lack of practicing exercises, and the need for practical data collection sessions. Emphasis should be given to early introduction of projects for data collection and analysis.